The Symbols of Belief in Dan Brown’s Angels and Demons (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2017)
Abstract The study aims to reveal what kind symbols of belief that were depicted by Dan Brown in the novel through the characters perspective. Therefore, this research uses a structuralism theory proposed by Joseph Campbell, The Hero’s Journey concept that had been elaborated by Christopher Vogler, which is to reveal Brown’s ideas through structuralist perspective. This research showed that there are ten symbols of belief, five of them (The Holy Bible, The Cross, Vatican City, The Pope, and Christmas) belong to Roman Catholic Church and the last five (Ambigram, Lucifer, Pyramid, Lingua Pura, and the four elements of science: Earth, Air, Fire and Water) belong to Illuminati brotherhood. Through those symbols of beliefs, it can be concluded that Roman Catholic Church (Religion) and Illuminati brotherhood (Science) are allies even they seek God in different ways. Keywords: Belief, symbol, Catholic Church, Illuminati, Science, Religion. . Abstrak Studi ini bertujuan untuk mengungkap simbol-simbol kepercayaan apa saja yang di gambarkan oleh Dan Brown di dalam novel ini melalui pandangan setiap karakter-karakter yang ada. Oleh karena itu, studi ini menggunakan a theory structural yang di temukan oleh Joseph Campbell, dengan konsep The Hero’s Journey yang mana telah di uraikan oleh Christopher Vogler, bertujuan untuk menguraikan ide-ide Brown melalui cara pandang strukturalis. Penelitian ini menunjukkan bahwa ada sepuluh symbol kepercayaan, lima di antaranya adalah (Kitab Bible, Salib, Vatikan, Paus, and Natal) yang mengarah pada Gereja Katolik Roma dan lima sisanya adalah (Ambigram, Lucifer, Piramid, Lingua Pura, dan empat elemen ilmu pengetahuan: Tanah, Udara, Api, dan Air) yang mengarah para Persaudaraan Illuminati. Melalui symbol-simbol kepercayaan tersebut, dapat di simpulkan bahwa Gereja Katolik Roma dan Illuminati adalah kawan meskipun mereka mencari tuhan dengan cara yang berbeda. Kata Kunci: Kepercayaan, Simbol, Gereja Katolik, Illuminati, Ilmu Pengetahuan, Agama.